Everyday Life and the Unconscious Mind. - Curtis, Hannah (Karnac Books, 2015)
An increasing number of people are seeking to develop an understanding of psychoanalytic concepts in order to apply them to the ordinary situations that they encounter as they go about their work, family and social lives. Some of these people are students just leaving college and going on to university, some are managers seeking to understand the dynamics of work place relationships and some are the friends or families of people who suffer with emotional distress or mental health issues. Everyday Life and the Unconscious Mind is written for students, for those who work in the care sector, or in.